Major liver resection in pregnancy: three cases with different etiologies and review of the literature. (17th January 2019) - Pencovich, Niv; Younis, Muhammad; Lessing, Yonatan; Zac, Lilach; Lessing, Joseph B.; Yogev, Yariv; Kupferminc, Michael J.; Nachmany, Ido
Abstract: Background: Major liver resection during pregnancy is extremely rare. When required, the associated physiologic and anatomic changes pose specific challenges and greater risk for both mother and fetus Materials and methods: Three cases of major liver resection during pregnancy due to different etiologies are presented. The relevant literature is reviewed and discussed. Results: We present three cases of major liver resection due to giant liver hemangioma with Kasabach–Merrit syndrome, giant hydatid cyst, and intrahepatic cholangiocarcinoma, at gestational week (GW) 17, 19, and 30, respectively. All patients had an uneventful postoperative course, continued the pregnancy and gave birth at GW 38. Conclusion: Major liver resection can be performed safely during pregnancy. A multidisciplinary team of surgeons, anesthesiologists and gynecologists, in a highly experienced tertiary hepatobiliary center, should be involved.